PENERAPAN MEDIA VIDEO PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI WAKTU PADA SISWA SEKOLAH DASAR - Rahayu, Rusnai; Harahap, Satwika Hartanti; Harahap, Mazdalifah; Nawawi, Rayhan (ELEMENTARY: Jurnal Inovasi Pendidikan Dasar, 2026)
This study aims to improve elementary school students’ learning outcomes in mathematics on the topic of time through the implementation of learning video media. The research problem is motivated by low student learning outcomes caused by conventional teaching methods and the lack of engaging instructional media. This study employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles. The research subjects were 25 fourth-grade elementary school students. Data collection techniques included observation of learning activities, learning achievement tests, interviews, and documentation. The results of the study indicated an improvement in students’ learning outcomes, as shown by an increase in the average score from 64 in Cycle I to 85 in Cycle II, as well as an increase in learning mastery from 60% to 92%. This improvement was influenced by the use of learning video media, which was able to visualize the concept of time in a concrete, engaging, and easily understandable manner. Therefore, the implementation of learning video media proved to be highly effective in improving elementary school students’ mathematics learning outcomes on the topic of time. ABSTRAK Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika materi waktu pada siswa sekolah dasar melalui penerapan media video pembelajaran. Permasalahan penelitian dilatarbelakangi oleh rendahnya hasil belajar siswa akibat pembelajaran yang masih bersifat konvensional dan kurangnya penggunaan media yang menarik. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) model Kemmis dan McTaggart yang dilaksanakan dalam dua siklus. Subjek penelitian adalah 25 siswa kelas IV sekolah dasar. Teknik pengumpulan data meliputi observasi aktivitas belajar, tes hasil belajar, wawancara, dan dokumentasi. Hasil penelitian ini menunjukkan adanya peningkatan hasil belajar siswa yang ditunjukkan oleh kenaikan nilai rata-rata dari 64 pada siklus I menjadi 85 pada siklus II, serta peningkatan ketuntasan belajar dari 60% menjadi 92%. Peningkatan tersebut dipengaruhi oleh penggunaan media video pembelajaran yang mampu memvisualisasikan konsep waktu secara konkret, menarik, dan mudah dipahami. Dengan demikian, penerapan media video pembelajaran terbukti sangat efektif dalam meningkatkan hasil belajar matematika siswa sekolah dasar pada materi waktu.